Conducting Polymers A New Era in Electrochemistry - Inzelt, György; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This second edition of a well-received volume has been thoroughly updated and expanded to cover the most recent developments. Coverage now includes additional polymers such as polyindole and polyazines, composites of polymers with carbon nanotubes, metals, and metal oxides, as well as bending-beam techniques for characterization. Again, the author provides a systematic survey of the knowledge accumulated in this field in the last thirty years. This includes thermodynamic aspects, the theory of the mechanism of charge transport processes, the chemical and physical properties of these compounds, the techniques of characterization, the chemical and electrochemical methods of synthesis as well as the application of these systems. The book contains a compilation of the polymers prepared so far and covers the relevant literature with almost 2000 references. From reviews of the previous edition ‘a comprehensive reference guide for those interested in this field’ (Journal of Solid State Electrochemistry).
Introduction -- Classification of Electrochemically Active Polymers -- Methods of Investigation -- Chemical and Electrochemical Syntheses of Conducting Polymers -- Thermodynamic Considerations -- Redox Transformations and Transport Processes -- Applications of Conducting Polymers -- Historical Background (Or: There Is Nothing New Under the Sun).
Keywords: Electrochemistry; Optical materials; Electronic materials; Polymers .; Materials science; Materials—Surfaces.; Thin films; Electrochemistry; Optical and Electronic Materials; Polymer Sciences; Characterization and Evaluation of Materials; Surfaces and Interfaces, Thin Films